KARAKTERISASI INDIKATOR KESESUAIAN LAHAN KOMODITI NANAS LOKAL (Ananas comosus) KABUPATEN MAJENE - Sanjaya, Muhammad Fahyu; Arham, Ihsan; Irlan, Irlan; Mahendra, Yusril; Irwansyah, Irwansyah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Indonesia boasts a high biodiversity, intricately linked to the various ecosystems within its territories. In Majene Regency, West Sulawesi Province, for instance, there is a unique commodity in the form of pineapple, locally known as 'pondang'. One of the efforts to preserve this unique pineapple commodity is to understand the characteristics of the cultivation land that has sustained it over time. This research aimed to characterize the land in the cultivation areas of Majene's local pineapple as fundamental information for farmers to comprehend the plant growth ecosystem and manage the land optimally. The research utilized purposive random sampling based on the cultivation locations of Majene's local pineapple. Observations revealed that the cultivation land conditions for Majene's local pineapple had an average temperature ranging from 25.65 to 29.75 ºC, rainfall between 1,488.05 and 2,820.50 mm, with humidity ranging from 63.38 to 89.00%. Additionally, soil fertility conditions in the research locations indicated high nutrient retention, as shown by slightly acidic to neutral soil pH values and high Cation Exchange Capacity (CEC), although some available nutrients indicated very low to low soil fertility levels, such as potassium. Soil management significantly influenced nutrient availability, soil salinity, and alkalinity in the research locations.